Ibolyák - Petőfi autográf kéziratának vizsgálata - Csikós Gréta; Petőfi Sándor (Szegedi Tudományegyetem Móra Ferenc Szakkollégiuma Szeged, 2022)
Although Sándor Petőfi’s oeuvre is undeniably one of the most known from Hungarian literature, there are still „blind spots” in our understanding of his life’s work. The Petőfi-prose has not been integrated into public education, nor among his works commonly known by the wider public audience. Although András Martinkó has, in 1965, processed the poet’s prosaic works, this monography does not yet know about a – from the perspective of the continuousness of the Petőfi-prose - important chain link. The Ibolyák autographic collection was only discovered 30 years later, in 1996. In it, there are two previously unknown novels, which show a close relation to Petőfi’s novel, A szökevények (1845) from a genre, formal and narratological aspect. The novels of Ibolyák put A szökevények in context. In my study I make an attempt to prove, that Petőfi’s unpublished novels, A bajazzo and A párbaj quasi prepare the path of his first novel published in print, A szökevények. They are the milestones of conscious poetical and genre experimentation. He attempted to translate the formal characteristics of the German Dialogroman – not unknown in Hungarian literary discourse – into short stories: his novels could be interpreted as genre experimentation attempting to move the boundaries of prosaic story telling into the direction of drama and ballade. The main elements of the thus created narrative language are the dialogue and the ellipse.
Keywords: Bölcsészettudományok; Nyelvek és irodalom